Role of Communication in the Process of a Better Socio Sanitary and Environmental Supervision of Artisanal Dyeing and Textile Activity in Burkina Faso: Case of the Craft Industries of Arrondissement Number 6 in the Commune of Ouagadougou, Burkina Faso - COMPAORE, Jérôme (Advances in Social Sciences Research Journal, 2022)
The current study was about the issue of the role that communication plays in the frame of a better organization of the socio-sanitary and environment sector of craft industry and textile in Burkina Faso, and which served the study object in arrondissement number 6 of the commune of Ouagadougou. This study aims at showing that the implementation of management mechanisms contributes to the use of efficient communication tools system. That one can help bringing up with a good organization in the processing chain of the dyeing activity, by protecting women and men working in the domain, and considering environment’s protection and our living area.